Heterogeneous Ni-Fe-P integrated with nickel foam as an efficient and durable electrocatalyst for water oxidation. (3rd May 2019) - Zhang, Jianshuo; Hou, Kun; Yao, Qianqian; Wu, Chuxin; Huang, Meihua; Guan, Lunhui
Abstract: Transition metal phosphides represent a class of promising electrocatalysts for electrochemical water oxidization and other energy conversion reactions. In this work, we report a novel seal strategy, followed by a second step phosphorization treatment, produces Ni-Fe-P heterostructure directly grown on nickel foam that shows highly catalytic activity for electrochemical water oxidation. The as-prepared catalyst exhibits an excellent electrocatalytic activity, manifested by a current density of 20 mA cm −2 with a very low overpotential (260 mV) for oxygen evolution reaction along with an extremely small Tafel slope of 27 mV decade −1 and a very excellent durability of 120 h in alkaline solution. The excellent performance with exceptional durability owe much to the synergistic effect between the Ni-Fe-P heterostructure and the outer oxidized layer. Remarkably, a current density of 10 mA cm −2 was reached at a low cell voltage of 1.63 V when the original electrode and surface oxidized electrode are used as cathode and anode, respectively. Graphical abstract: Image 1 Highlights: NiFeP heterostructure is prepared for electrochemical water splitting. Seal strategy is used for the preparation of NiFeO precursor. The catalyst runs continuously for at least 120 h under OER operation. The electrolytic cell only needs 1.63 V to reach a current density of 10 mA cm −2 .